Implementation of Profile Matching in the Decision Support System for Best Student Selection - Rumandan, Rhaishudin Jafar; Nuraini, Rini; Sari, Marliana (Forum Kerjasama Pendidikan Tinggi, 2022)
The determination of outstanding students is carried out by schools, which provide scholarships to their students in order to provide motivation to improve their academic achievement. The selection of the best students is usually done by looking at the student's report card scores, followed by the homeroom meeting. This is considered not objective and requires a long time to select the best students. Through a decision-support system, the best students can be selected based on the best criteria and alternatives. In a decision support system, a method is needed to determine the best alternative. The profile matching method is considered to have a better level of objectivity because, to measure the value of each indicator, the valuation variable is derived again with sub-indicators and is weighted using assessment parameters. This study aims to solve the problem of selecting the best student through a decision-support system with the output in the form of a ranking using the profile matching method. Based on the calculation of profile matching, it shows that the results of calculating the final score of the best student 1 are a final score of 3.000, the best student 2 gets a final score of 2.955, and the best student 3 gets a final score of 2.693. From the final score, first place in the selection of the best student was Putri Nurlandari with a final score of 3.000.